Magnetic properties in α-MnO2 doped with alkaline elements - Tseng, Li-Ting; Lu, Yunhao; Fan, Hai Ming; Wang, Yiren; Luo, Xi; Liu, Tao; Munroe, Paul; Li, Sean; Yi, Jiabao (Scientific reports, 2015)
α-MnO 2 nanotubes were fabricated using a hydrothermal technique. Li, Na and K ions were introduced into MnO 2 nanotubes to tailor their magnetic properties. It was found that with a doping concentration lower than 12 at%, the nanotubes showed ferromagnetic-like ordering at low temperature (<50 K), while antiferromagnetic coupling dominated their physical behavior with doping concentrations beyond 12 at%. Such experimental phenomenon was in very good agreement with associated first principle calculations. The ferromagnetic-like ordering originates from the breaking of equivalence between two different Mn-O octahedrals in α-MnO 2 due to the filling of alkaline ions in the tunnels. Both small charge transfer and lattice distortion play important roles in the ferromagnetic ordering.